Animal rights - Baka, A.; Ntorli, V.; Argyri, P. (Open Schools Journal for Open Science, 2020)
Most of educational projects are related with challenges of environmental issues and rarely taking under consideration that animals are part of life of land. Animals have a strong effect in our lives, as keep the life cycle balances. That is why in our project we decided to concern ourselves with Animal Rights, all around the world and in Greece. The main problems we are dealing with are: The living conditions of productive animals, the rights of stray animals, the abuse of animals, the torture of equine animals and animals which produce fur, the conduct of experimental medical tests on animals and the protection of endangered animals. In our project we have set some goals as well as the means of meeting them. When it comes to finding a solution to the problems mentioned above, after noticing what our classmates knew about them, we came to the realization that what is needed most of all is better information about these problems that can be found in an easy, fun and interactive platform. As a team, we made various games and activities with which people can learn about animals and the difficult situations they are dealing with.